2019
DOI: 10.1108/hff-09-2019-0671
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of thermal pulsating alumina/water nanofluid flow over three different cross-sectional channel

Abstract: Purpose The purpose of this study is to investigate the pulsating flow in a three-dimensional channel. Channel flow is laminar and turbulent. After validation, the effect of different channel cross-sectional geometries (circular, hexagonal and triangular) with the pulsating flow are investigated. For this purpose, the alumina nanofluid was considered as a working fluid with different volume percentages (0 per cent [pure water], 3 per cent and 5 per cent). Design/methodology/approach In this study, the pulsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…We first give examples of static structure factors with the same electric field strength under different driving forces ( Fig 5 ). Under the action of a strong electric field E = 0.06 and a strong driving force F = 0.0005, the static structure factor S ( G 1 )/ S (0) in the plane oscillates, is attenuated, and a peak appears at the lattice vector [ 31 ]. This sharp peak shows that the water has a certain degree of order, but the water molecules have not yet crystallised.…”
Section: Resultsmentioning
confidence: 99%
“…We first give examples of static structure factors with the same electric field strength under different driving forces ( Fig 5 ). Under the action of a strong electric field E = 0.06 and a strong driving force F = 0.0005, the static structure factor S ( G 1 )/ S (0) in the plane oscillates, is attenuated, and a peak appears at the lattice vector [ 31 ]. This sharp peak shows that the water has a certain degree of order, but the water molecules have not yet crystallised.…”
Section: Resultsmentioning
confidence: 99%
“…The numerical outputs indicated that the derived formulation given in Equation 6exhibited better prediction performance compared to the comparative equation-4 (CE-4) and the comparative equation-5 (CE-5). Finally, from the numerical point of view, it is also noted that some useful recent investigations can be found in the field of thermal energy storage, 19 nanofluid flow, 20,21 low-fluid pressure safety valve design, 22 heat transfer, 23 and thermal analysis. 24…”
Section: Numerical Comparisonmentioning
confidence: 99%
“…The scientists explored the heat-pulsed alumina/H2O nanofluid field in a 3D duct, and their findings revealed that increasing the size percentage of Al2O3 particle lowers the fluid temperature, however, using the nanofluid produces a pressure reduction in the channel [13,14]. Valuable studies received by Jajja et al [15] and Manova et al [16] in different situations as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%